Pembelajaran Integratif Sains dan Al-Quran Revitalisasi Nilai Ajaran Islam dan Pembentukan Karakter di SMA Trensains Sragen - Azalia Mutammimatul Khusna; Annur Indah Sari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
The education about science was very important to create students character in order to beÃ‚ faithful and pious to God, that was because the existence of the truth about creation verses and itsÃ¢â‚¬â„¢ process. In this case, the figure of science, a moslem scientist, Ibn Taymiyah, which his theory about creation was used by an education institution in Central Java to apply character based education from the study of science. The writer used field research method to know about the plot of the science education which apllied in the school. The aim is to know how far the integrative education between Scince and Al QurÃ¢â‚¬â„¢anÃ‚ is in creating the good character of students. The object is the students of Darul Ihsan Muhammadiyah Trensains Highschool who practiced about science in the laboratorium or out of class. The result is that the active students in the science study based on Al QurÃ¢â‚¬â„¢an and character were well mannered, has better attitude than their friends and more faithful.